High-moisture-absorption high-moisture-retention medicine-loading medical dressing and preparation method thereof

Through the composite technology of calcium alginate hydrogel and fiber skeleton, the problems of precipitation and shedding of drugs in the hydrogel layer are solved, effective embedding and sustained release of drugs are achieved, water absorption and moisturizing properties of the dressing are improved, the effectiveness of the drug is extended, and the healing speed and quality of the wound are improved.

CN119857164AActive Publication Date: 2025-04-22TIANJIN KANGWEI QIXIN TECHNOLOGY CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510047707.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

In the prior art, the drug is precipitated, shedded, evaporated, oxidized or deteriorated in the hydrogel layer, resulting in poor effect of the dressing during storage and use.

Method used

Calcium alginate hydrogel is used to combine with the fiber skeleton, and the drug components are attached to the fiber surface through physical adsorption and are embedded by the calcium alginate hydrogel to form a honeycomb structure to ensure effective protection and sustained release of the drug.

Benefits of technology

It realizes effective embedding and sustained release of the drug, improves the water absorption and moisturizing properties of the dressing, extends the effectiveness of the drug, and improves the healing speed and quality of the wound.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857164A_ABST
    Figure CN119857164A_ABST
Patent Text Reader

Abstract

The invention provides a medical dressing with high water absorption, high moisture retention, a drug loading function and good mechanical properties and a preparation method thereof. The medical dressing comprises a fiber skeleton and a hydrogel film, the fiber skeleton loads medicine components, calcium alginate hydrogel forms the hydrogel film on the fiber surface, the medicine components loaded on the fiber skeleton are embedded by the hydrogel film, gaps or grooves in the fiber surface are filled with medicine, and the hydrogel film is formed by calcium alginate hydrogel. After embedding, original gaps of the fiber skeleton are reserved, and the hydrogel film forms a honeycomb structure. The fiber skeleton provides required mechanical properties for the dressing, is used as a carrier of drug components, and has the remarkable advantages of wide adaptability to the drug components and large drug loading capacity. The hydrogel film swells when encountering water, and the medicine is continuously released. The hydrogel and fiber porous structure provides excellent moisture absorption and moisture retention performance for the dressing. The device can be designed into a gauze type, a porous foam type, an application type and the like according to needs, and has wide adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical devices, and in particular to a medical dressing capable of carrying medicine. Background Art

[0002] Dressings should provide a moist healing environment for the wound surface, maintain water absorption and air permeability, absorb wound exudate in a timely manner, promote the synthesis and secretion of growth factors, and accelerate wound healing. Drug loading can help the wound surface prevent infection, eliminate inflammatory reactions, and improve the healing speed and quality.

[0003] Dressings are generally fiber fabrics, such as gauze, non-woven fabrics, etc. The hydrogel is compounded with gauze so that the dressing has both good mechanical properties and the advantages of high moisture absorption and anti-adhesion. Chinese invention patent CN202111467950.1 discloses a method for preparing hydrogel gauze that prevents blood adhesion, which retains the characteristics of gauze and has the advantages of hydrogel preventing blood adhesion. Chinese invention patent CN202111143272.3 provides a surface hydrophilically modified chitosan porous gel hemostatic gauze, in which chitosan gel is deposited on the gauze, and the provided hemostatic gauze has good mechanical strength, stability and can quickly stop bleeding.

[0004] Hydrogels can carry drugs, giving the dressings antibacterial, anti-inflammatory or therapeutic functions. Chinese utility model patent CN201821034714.4 discloses a leak-proof hydrogel composite gauze, which places drug-loaded gel particles between two layers of gauze and uses a shredded fiber layer to prevent gel particles from leaking. The dressing has antibacterial function, but the drug is separated from the wound by shredded fibers and gauze, making it difficult for the drug to be released into the wound. Chinese utility model patent CN201720989627.3 provides an anti-adhesion, highly hygroscopic antibacterial gauze, with a gel layer applied on the surface of the gauze, the gel layer containing an antibacterial liquid, and the gel layer and the gauze are bonded by a polymer binder.

[0005] In the prior art, the gel layer drug loading mainly has the following problems:

[0006] 1. More than 97% of the hydrogel colloid is water. After the hydrogel layer is freeze-dried into a film, a thin-walled mesh structure is formed. Since the pore wall is extremely thin, only a dozen microns, if the drug content is high or unevenly dispersed, it will cause the drug to precipitate and adhere to the thin wall surface and cannot be embedded, causing the drug components to contact the external environment. During the storage period, the dressing will experience problems such as shedding, volatilization, oxidation, and deterioration.

[0007] 2. Dissolve or disperse the drug in a polymer matrix to form drug-loaded microspheres, which can effectively protect the drug. Disperse the drug-loaded microspheres into the gel. After film formation, the microspheres adhere to the pore wall or are half-embedded in the pore wall. The drug content in the microspheres is between 1-15%. However, the preparation process of drug-loaded microspheres is complicated, and the drug embedding rate (the ratio of the drug content in the microspheres to the amount of drug delivered) generally does not exceed 50%, which greatly increases the manufacturing cost.

[0008] 3. Direct mixing of drugs or drug-loaded microspheres into gel will affect the film-forming properties of the gel. Currently, the proportion of drugs used for gel film loading is generally no more than 1%. The drug loading is low, the half-life of the effective concentration released to the wound surface is short, and a sustained and stable therapeutic effect cannot be formed. Summary of the invention

[0009] The purpose of the present invention is to overcome the deficiencies in the prior art and to provide a medical dressing with high moisture absorption, high moisture retention, high drug loading efficiency and long-term sustained drug release.

[0010] In order to achieve the above object, the present invention provides a medical dressing, comprising a fiber skeleton and a hydrogel film, wherein the fiber skeleton carries a drug component, and calcium alginate hydrogel forms the hydrogel film on the surface of the fiber skeleton, wherein the drug component carried by the fiber skeleton is embedded in the hydrogel film, and the drug is filled in the gaps or grooves on the fiber surface, and the original gaps of the fiber skeleton are retained after embedding. The hydrogel film forms a honeycomb structure.

[0011] Preferably, the mass percentage of the calcium alginate hydrogel to the fiber skeleton is 10-22%.

[0012] Preferably, any of the above items is that the thickness of the calcium alginate hydrogel film formed on the surface of the fiber skeleton is 8-14 μm, and the content of the drug component is less than 25% of the weight of the fiber skeleton.

[0013] Preferably, in any of the above items, the porosity of the fiber skeleton is 90%-95%, and the average pore size of the fiber skeleton is between 35-100 μm.

[0014] In the present invention, the fiber skeleton is a skeleton material of the dressing composed of fibers.

[0015] Preferably, in any of the above items, the material of the fiber skeleton is selected from gauze and / or non-woven fabric.

[0016] Preferably, in any of the above items, the fiber component of the fiber skeleton is preferably at least one of cotton fiber, linen fiber and viscose fiber.

[0017] Preferably, the fiber skeleton is in the form of gauze; preferably, the fiber skeleton is a nonwoven fabric; preferably, the gauze is absorbent medical gauze; preferably, the nonwoven fabric is a spunlace nonwoven fabric; the spunlace nonwoven fabric fibers are further preferably biomass cellulose fibers such as cotton fibers, hemp fibers, and artificial viscose fibers. Cellulose fibers have excellent water absorption and biocompatibility; cotton fibers and hemp fibers have rich microporous structures, and viscose fibers have grooves on their surfaces. The micropores or grooves on the fiber surface provide volume for drug loading, making them ideal carriers for drug ingredients. Preferably, the surface density of the spunlace nonwoven fabric is 30-80g / m 2 The porosity is within 90%-95%, and the average pore size is between 35-72μm.

[0018] In the present invention, the fiber skeleton is used as a carrier for loading drug components, and the drug components are attached to the surface of the fiber by physical adsorption without forming chemical bonds, so as to facilitate drug release. The drug content generally does not exceed 25% of the fiber weight. Too high a drug content is not conducive to the complete embedding of the drug by the hydrogel membrane.

[0019] In the present invention, calcium alginate hydrogel forms a gel film on the fiber surface, the drug components loaded by the fiber skeleton are embedded, the original gaps of the fiber skeleton are retained, and the gel film forms a honeycomb structure.

[0020] In the present invention, the percentage of calcium alginate to fiber skeleton mass is controlled between 10-22%, and the film thickness of calcium alginate hydrogel on the fiber surface is controlled between 8-14 μm, ensuring effective drug embedding and maintaining the flexibility of the dressing.

[0021] When the medical dressing provided by the present invention is used, calcium alginate combines with sodium ions in body fluids to generate sodium alginate gel with high water absorption and high moisturizing properties, sodium alginate swells, the distance between macromolecules increases, and the embedded drug migrates and penetrates in the gel and is continuously released to the wound surface. Preferably, when used, a solution containing sodium ions (such as saline) can be sprayed on the medical dressing in advance to achieve drug release.

[0022] The medical dressing provided by the present invention can be laminated to form a conformable dressing, and its structure is as follows: the bottom layer is the medical dressing of the present invention, and the upper layer is a soft and fluffy fiber fabric.

[0023] The present invention also provides a method for preparing the medical dressing described in any one of the above items, comprising the following steps:

[0024] Step 1: preparing a hydrogel; dissolving sodium alginate powder in deionized water, stirring until completely dissolved, and eliminating bubbles, to obtain a sodium alginate aqueous solution;

[0025] Step 2: The form of the fiber skeleton (gauze or nonwoven fabric) and the selection of fiber materials;

[0026] Step 3: drug loading treatment of fiber skeleton;

[0027] Step 4: Compounding the hydrogel with the fiber skeleton: placing the drug-loaded fiber net obtained in step 3 on a transmission device, spraying the sodium alginate aqueous solution obtained in step 1 onto the drug-loaded fiber net through a nozzle; after the sodium alginate solution fully infiltrates the surface of the drug-loaded fiber net, the drug-loaded fiber net is removed from the transmission device and then immersed in a calcium chloride aqueous solution; sodium alginate and calcium ions are cross-linked and cured to form water-insoluble calcium alginate, forming an embedding film on the surface of the drug-loaded fiber net; after curing, washing with water to remove reaction byproducts; and blowing air to control the moisture content;

[0028] Step 5: Drying: freeze drying is used for drying.

[0029] Preferably, in step 1, the mass concentration of the sodium alginate aqueous solution is 1-3%, the solution viscosity should be less than 1000 mPa·s; the dissolution temperature is 22-50° C.; and the sodium alginate M / G mass ratio is 2.5-3.10.

[0030] Preferably, in any of the above items, in step 2, the material of the fiber skeleton is selected from gauze and / or non-woven fabric.

[0031] Preferably, in any of the above items, in step 2, the fiber component of the fiber skeleton is preferably at least one of cotton fiber, linen fiber, and viscose fiber.

[0032] Any of the above items is preferably that, in step 3, the drug is a water-soluble drug, and the processing step is step a: dissolving the water-soluble drug in deionized water, and loading the drug onto the fiber skeleton by a padding process or a spraying method to obtain a drug-loaded fiber mesh. Further preferably, step 3 also includes a drying step; preferably, in step 3, the drug is a heat-stable water-soluble drug, and the drug-loaded fiber mesh obtained in step a is subjected to a thermal drying method. After drying, the moisture content of the drug-loaded fiber mesh (the percentage of water content weight to wet weight of the drug-loaded fiber mesh) is controlled to be 18-25%; preferably, in step 3, the drug is a water-soluble drug that is easily volatile when heated, and the drug-loaded fiber mesh obtained in step a is subjected to a freeze-drying method. After drying, the moisture content of the drug-loaded fiber mesh is controlled to be 18-25%.

[0033] Preferably, in any of the above items, in step 3, the drug is an oil-soluble drug, and the treatment step is step b: selecting an oil-in-water surfactant, adding the oil-in-water surfactant and the oil-soluble drug to deionized water, and stirring at high speed to form an oil-in-water emulsion; and loading the oil-in-water emulsion onto the fiber skeleton by a padding process or a spraying method.

[0034] Any of the above is preferably that in step 4, the time for the drug-loaded fiber mesh to be removed from the nozzle position of the sodium alginate aqueous solution to the transmission device is 25-35s; the mass concentration of the calcium chloride aqueous solution is 6-12%, and the coagulation time of the drug-loaded fiber mesh in the calcium chloride aqueous solution is 5-8 minutes.

[0035] Preferably, in any of the above items, in step 5, the freeze-drying temperature is -20°C to -30°C, and the time is 24 hours.

[0036] In a preferred embodiment of the present invention, in step 1, the method for preparing the hydrogel solution is preferably as follows: dissolving sodium alginate powder in deionized water at a temperature in the range of 22-50° C. Stirring until completely dissolved and bubbles are eliminated to obtain a sodium alginate solution.

[0037] Preferably, the mass concentration of the sodium alginate aqueous solution is 1-3%, and the solution viscosity should be less than 1000 mPa·s.

[0038] The raw material for preparing the hydrogel of the invention is sodium alginate, which is a natural polysaccharide formed by linking β-D-mannuronic acid (M sugar) and α-L-glucuronic acid (G sugar). Sodium alginate combines with calcium ions to form a calcium alginate gel with a cross-linked structure. When it contacts with pus and blood in a wound, sodium ions of the human body exchange ions with calcium alginate ions. With the entry of sodium ions, water-insoluble calcium alginate is converted into water-soluble sodium alginate. A large amount of water enters the medical dressing to form a colloid, forming a layer of moist hydrogel, providing a moist healing environment for the wound surface and providing good conditions for cell growth.

[0039] Sodium alginate is stable in nature, does not reduce the activity of drugs, is safe and biocompatible, has good film-forming properties, and the film has good softness.

[0040] In the present invention, sodium alginate is preferably a sodium alginate gel with a high M / G ratio, and the preferred M / G mass ratio is in the range of 2.5-3.10. The hydrogel prepared from sodium alginate in this M / G range is relatively soft and has a strong creep recovery ability.

[0041] In a preferred embodiment of the present invention, in step 2, the preferred scheme of the fiber skeleton material is: the fiber skeleton material is selected according to the application requirements of the dressing: preferably gauze or non-woven fabric; preferably fiber material, more preferably natural cellulose fiber, more preferably at least one of cotton fiber, hemp fiber, and viscose fiber. Cotton fiber and hemp fiber have rich microporous structures, and viscose fiber has grooves on its surface, which are ideal carriers of drug ingredients. Cellulose fiber has excellent water absorption and biocompatibility.

[0042] In a preferred embodiment of the present invention, in step 3, the drug loading treatment scheme of the fiber skeleton material is preferably:

[0043] According to needs, the drug in the drug loading treatment is selected from at least one of antibacterial, cytokine, hemostatic, anti-inflammatory and analgesic drugs.

[0044] In step 3, the solution for water-soluble drug loading is preferably:

[0045] The water-soluble drug is dissolved in deionized water, and the solution concentration is determined according to the drug solubility and drug loading requirements.

[0046] The drug is loaded onto the fiber skeleton material through a padding process to obtain a drug-loaded fiber mesh. The number of padding is greater than or equal to one time, and the drug loading can be increased after multiple padding. Preferably, a spraying method is used to load the drug onto the fiber skeleton. Preferably, a heat-stable drug can be dried by heat; preferably, a drug that is easily volatile when heated can be dried by freeze drying; preferably, the moisture content of the drug-loaded fiber mesh after drying is controlled at 18-25%.

[0047] In step 3, the solution for oil-soluble drug loading is preferably:

[0048] An oil-in-water (O / W) surfactant is selected, and the O / W surfactant and an oil-soluble drug are added to deionized water, and stirred at high speed to form a stable O / W emulsion. The O / W surfactant can help disperse oil in water to form an O / W emulsion system, in which oil is used as an internal phase and water is used as a continuous external phase.

[0049] The benefits of forming an oil-in-water emulsion system are: 1) cellulose fibers have good water absorption, and the oil-in-water (O / W) emulsion can be uniformly adsorbed on the fiber surface; 2) it is beneficial for the subsequent film formation of the sodium alginate aqueous solution on the fiber surface; 3) the present invention utilizes an oil-in-water emulsion system to overcome the defects of the prior art. If an organic solvent is used to dissolve an oil-soluble drug, the solvent needs to be volatilized and removed after the drug is loaded onto the fiber, which increases processing costs and causes environmental damage.

[0050] Preferably, the water-in-oil type surfactant is preferably Span 80, Wacker E1049, food and drug industry silicone oil emulsion, poloxamer F127aeo-9 emulsifier, polyethylene glycol (PEG) 200-6000, etc. The water-in-oil type surfactant has no odor and good biocompatibility. The use of the water-in-oil type surfactant in the present invention is widely used in the medical field, which is conducive to improving the solubility and absorption rate of the drug, thereby enhancing the effect of the drug.

[0051] In a preferred embodiment of the present invention, in step 4, the preferred scheme for compounding the hydrogel with the fiber skeleton is:

[0052] In step 3, the drug-loaded fiber web is placed on the conveyor roller 1, and the conveyor roller 1 rotates to spread the drug-loaded fiber web on the conveyor belt 3. The conveyor roller 1 and the mobile platform (conveyor belt 3) run at the same speed to achieve tension-free conveyance of the fiber web.

[0053] A horizontal row of nozzles 4 is arranged above the conveyor belt, and the sodium alginate aqueous solution prepared in step 1 is sprayed onto the drug-loaded fiber mesh through the nozzles 4 .

[0054] According to the set final content of the hydrogel and the square meter gram weight of the fiber mesh, the mass concentration of the sodium alginate aqueous solution (in the range of 1-3%), the nozzle flow rate, and the movement speed of the drug-loaded fiber mesh are regulated. The nozzle flow rate is controlled to control the mass percentage of the calcium alginate hydrogel and the fiber skeleton contained in the final medical dressing to be 10-22%; the movement speed of the fiber mesh is controlled so that the time from the nozzle 4 position to the removal of the drug-loaded fiber mesh from the conveyor belt is controlled to be 25-35s, preferably 30s, to ensure that the sodium alginate solution is fully infiltrated on the fiber surface.

[0055] After the drug-loaded fiber web moves out of the conveyor belt 3, it enters the curing bath 5 under the action of gravity. The curing bath 5 contains a calcium chloride aqueous solution. Sodium alginate and calcium ions are cross-linked and cured to form water-insoluble calcium alginate, forming an embedding film on the surface of the drug-loaded fiber web.

[0056] Preferably, the mass concentration of the calcium chloride aqueous solution is 6-12%; preferably, the solidification time of the drug-loaded fiber mesh in the solidification bath 5 is 5-8 minutes. The solidification bath 5 is provided with a liquid outlet and an inlet to keep the calcium ion concentration constant.

[0057] When the set solidification time is reached, the take-up roller 14 is operated to transfer the fiber web to the washing tank 9 to remove the reaction byproducts of chloride ions and sodium ions.

[0058] The washed drug-loaded fiber web passes through the airflow nozzle 12 of the blowing device to control the moisture content of the fiber web and ensure that there are no water drops when the fiber web is rolled up.

[0059] The process of the present invention realizes the continuous production of composite solidification of fiber mesh and hydrogel, and the fiber mesh is not subjected to tensile tension and mechanical extrusion before being removed from the solidification bath 5, thereby ensuring that the drug loaded on the mesh surface does not penetrate into the sodium alginate aqueous solution.

[0060] In a preferred embodiment of the present invention, in step 5, the drying is preferably a freeze-drying process, and freeze-drying is performed after cross-linking and curing. The use of freeze-drying can prevent the drug components from being damaged by high-temperature drying. Preferably, the freeze-drying temperature is -20°C to -30°C; preferably, the time is 24 hours.

[0061] In a preferred embodiment of the present invention, the preparation method of the present invention further comprises step 6, a post-finishing step:

[0062] Preferably, the medical dressing after drying in step 5 is smoothed and soft, sterilized, and packaged as required.

[0063] Preferably, the medical dressing is bonded to an adhesive film to form a patch-type dressing.

[0064] Preferably, the medical dressing is laminated with hot air cotton, which is a highly fluffy and soft hot-melt fiber material, and is dot-matrix thermally bonded to the above-mentioned dressing by laser to form a sponge-type dressing.

[0065] The present invention uses sodium alginate as the preparation material of the hydrogel, and ensures that the medical dressing has safety and biocompatibility without reducing the activity of the drug, and has good film-forming performance, and the film has good softness. At the same time, the present invention loads the drug on the fiber skeleton, so that the drug is embedded in the inside of the gel layer, so that the drug is effectively protected. At the same time, by controlling the drug loading, the type of hydrogel, and the ratio of the hydrogel to the skeleton fiber, it is ensured that the drug loaded on the skeleton fiber does not lose during the gel coating process, and the effective release of the drug during use is ensured.

[0066] The significant advantages and beneficial technical effects of the present invention are:

[0067] 1. Using fiber aggregate as the skeleton material provides excellent mechanical properties for the dressing. Through the reasonable design of the skeleton material, the dressing can have the required mechanical properties, such as strength, elasticity, softness and expansion.

[0068] 2. As a drug carrier, the fiber skeleton has a wide adaptability to the ingredients of the drug, and is suitable for both water-soluble and oil-soluble liquids. It has a large drug loading capacity, which is more than 10 times higher than that of the hydrosol gel film.

[0069] 3. The hydrogel gives the dressing excellent water absorption and moisturizing properties, greatly improving the water absorption and moisturizing properties of the auxiliary materials.

[0070] Compared with traditional gauze, the moisture content is increased by 111.19% and the moisturizing time is increased by 418.18%.

[0071] 4. The drug components are isolated from the outside world by a dense polymer film, which effectively protects the drug components from volatilization, oxidation and deterioration, greatly extending the shelf life of the dressing.

[0072] 5. When the dressing comes into contact with body fluids, the hydrogel turns into a sol, and the drug release is stable and lasting.

[0073] 6. The dressing of the present invention can be stacked, rolled or balled like traditional gauze, and can be used for hemostasis and bandaging of wounds. It can be made into dressings, facial masks and foam dressings, and has a wide range of uses.

[0074] 7. The present invention realizes the continuous production of composite solidification of fiber mesh and hydrogel, and before the fiber mesh enters the solidification bath, it is not subjected to stretching and mechanical extrusion, ensuring that the drug loaded on the surface of the mesh does not penetrate into the sodium alginate aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 This is a structural diagram of a preferred medical dressing of the present invention.

[0076] Figure 2 This is the preferred hydrogel and fiber skeleton composite process and technology of the present invention.

[0077] Figure 3 The moisture release curve of the dressing in the preferred embodiment 4 of the present invention.

[0078] Figure 4 This is the drug release curve of the dressing in preferred embodiment 4 of the present invention.

[0079] Figure 5 This is a schematic cross-sectional view of the drug-loaded retroperitoneal fiber in preferred embodiment 1 of the present invention.

[0080] Markings in the accompanying drawings: 1 conveying roller, 2 guide roller, 3 conveyor belt, 4 nozzle, 5 curing bath, 6 guide roller, 7 guide roller, 8 guide roller, 9 washing tank, 10 guide roller, 11 guide roller, 12 air flow nozzle, 13 guide roller, 14 winding roller. DETAILED DESCRIPTION

[0081] The present invention is further described in detail below through the accompanying drawings and specific embodiments.

[0082] like Figure 1 Shown is a structural diagram of a medical dressing provided by the present invention. Figure 5 Shown is a schematic diagram of the cross-section of drug-loaded retroperitoneal fibers.

[0083] The fiber skeleton is used as a carrier for loading drug components. The drug components are attached to the surface of the fiber by physical adsorption without forming chemical bonds, so as to facilitate drug release; Figure 1 a shows drug-loaded fiber mesh. Figure 1 The enlarged single fiber in a has a diameter of 20 μm.

[0084] Calcium alginate hydrogel forms a film on the fiber surface, the drug components loaded by the fiber skeleton are embedded, the original gaps of the fiber skeleton are retained, and the gel film forms a honeycomb structure, such as Figure 1 b shows the hydrogel-embedded fiber surface drug. Figure 1 The enlarged image of a single fiber in b is 21 μm.

[0085] The medical dressing provided by the present invention can be laminated, such as Figure 1 c shows a sponge-type dressing made of medical dressing and hot air cotton.

[0086] Figure 2 The figure shows the process and technology schematic diagram of the hydrogel and fiber skeleton composite process of the present invention. Figure 2 The process flow of step 4 shown is for the composite process of hydrogel and fiber skeleton:

[0087] In step 3, the drug-loaded fiber web is placed on the conveyor roller 1, and the conveyor roller 1 rotates to spread the drug-loaded fiber web on the conveyor belt 3. The conveyor roller 1 and the mobile platform (conveyor belt 3) run at the same speed to achieve tension-free conveyance of the fiber web.

[0088] A horizontal row of nozzles 4 is arranged above the conveyor belt, and the sodium alginate aqueous solution prepared in step 1 is sprayed onto the drug-loaded fiber mesh through the nozzles 4 .

[0089] According to the set final content of the hydrogel and the square meter gram weight of the fiber mesh, the mass concentration of the sodium alginate aqueous solution (in the range of 1-3%), the nozzle flow rate, and the movement speed of the drug-loaded fiber mesh are regulated. The nozzle flow rate is controlled to control the mass percentage of the calcium alginate hydrogel and the fiber skeleton contained in the final medical dressing to be 10-22%; the movement speed of the fiber mesh is controlled so that the time from the nozzle 4 position to the removal of the drug-loaded fiber mesh from the conveyor belt is controlled to be 25-35s, preferably 30s, to ensure that the sodium alginate solution is fully infiltrated on the fiber surface.

[0090] After the drug-loaded fiber web moves out of the conveyor belt 3, it enters the curing bath 5 under the action of gravity. The curing bath 5 contains a calcium chloride aqueous solution. Sodium alginate and calcium ions are cross-linked and cured to form water-insoluble calcium alginate, forming an embedding film on the surface of the drug-loaded fiber web.

[0091] Preferably, the mass concentration of the calcium chloride aqueous solution is 6-12%; preferably, the solidification time of the drug-loaded fiber mesh in the solidification bath is 5-8 minutes. The solidification bath 5 is provided with a liquid outlet and an inlet to keep the calcium ion concentration constant.

[0092] When the set solidification time is reached, the take-up roller 14 is operated to transfer the fiber web to the washing tank 9 to remove the reaction byproducts of chloride ions and sodium ions.

[0093] The washed drug-loaded fiber web passes through the air flow nozzle 12 to control the water content of the fiber web.

[0094] Figure 2In the process, guide rollers 2, 6, 7, 8, 10, 11 and 13 control the running direction of the drug-loaded fiber web.

[0095] Example 1

[0096] Embodiment 1 provides a preferred medical dressing of the present invention, which is composed of the following components:

[0097] Fiber skeleton: 100% viscose spunlace nonwoven fabric, weight 40g / m 2 ;

[0098] Drug ingredients: Tea polyphenols, polyphenols have antibacterial, antioxidant, anti-inflammatory characteristics, and have good biological safety. Tea polyphenols solution 2.65%, room temperature.

[0099] Embodiment 1 The preferred preparation method is:

[0100] Prepare 2% sodium hyaluronate algae aqueous solution, heat to 50°C, stir thoroughly and eliminate bubbles.

[0101] After two dipping and two rolling by the dipping and rolling equipment, the fiber skeleton material loaded with tea polyphenol drug components was obtained, and the final content of tea polyphenols was 13.8%.

[0102] The hydrogel and the fiber skeleton are compounded by the process of the present invention (step 4). The time from the fiber skeleton from the nozzle to the conveyor flat belt is 32 seconds. The curing time in the curing bath is 6 minutes, and the appropriate concentration of calcium chloride in the curing bath is 8%.

[0103] According to step 5, the freeze-drying process is used for drying, and the freeze-drying is carried out at -20°C for 24 hours.

[0104] Perform post-processing according to step 6, including flatness and softness finishing, sterilization, packaging, etc.

[0105] Example 2

[0106] Embodiment 2 provides a preferred medical dressing of the present invention, which is composed of the following components:

[0107] Fiber skeleton: medical absorbent cotton gauze.

[0108] Drug ingredients: Lemon essential oil. Lemon essence has significant antibacterial, anti-inflammatory and antipyretic effects. The limonene in it is particularly beneficial for whitening, astringency, and balancing oil secretion.

[0109] Surfactant: Methyl silicone oil, also known as ordinary silicone oil, has good chemical stability and insulation properties.

[0110] According to the ratio of cinnamon oil to methyl silicone oil of 1:3, cinnamon oil emulsion was prepared, and the cinnamon oil content in the emulsion was 2%. Stirring was carried out at room temperature and 1200r / min for 10 hours to form a stable water-in-oil emulsion.

[0111] Prepare 1% sodium hyaluronate aqueous solution, heat to 50°C, and stir thoroughly.

[0112] The hydrogel and the fiber skeleton are compounded by the process of the present invention (step 4). The time from the fiber skeleton from the nozzle to the conveyor flat belt is 35 seconds. The curing time in the curing bath is 8 minutes, and the appropriate concentration of calcium chloride in the curing bath is 8%.

[0113] According to step 5, freeze-dry at -20 °C for 24 hours and finish according to step 6.

[0114] Example 3

[0115] In Example 3, the medical dressing obtained in Example 2 and the hot air cotton are used to make a sponge-type dressing. The dressing obtained in Example 2 is layer A, and the hot air cotton is layer B. Figure 1 c shows the structure of sponge dressing. The hot air cotton is a fluffy and soft fiber net made of ES fiber, with a weight of 80g / m 2 The two layers are thermally bonded by laser dot matrix.

[0116] Implementation 4

[0117] Example 4 Performance test of the obtained medical dressing:

[0118] 1) Comparison of water absorption and moisturizing performance

[0119] After the material is completely wetted, the moisture content is measured, and the moisture is released under the atmospheric conditions of room temperature of 22.5°C and relative humidity of 60%, and the moisture release curve is obtained, such as Figure 3 shown.

[0120] The water absorption rate of the medical gauze and sodium alginate composite system prepared by the method of the present invention (sodium alginate content 22.96%, preparation method is similar to Example 1 or 2) is 677.37%, and the time for dehumidification to reach a moisture content of 18.02% is 285 minutes. The water absorption rate of gauze of the same specification is 320.74%, and the time for dehumidification to reach a moisture content of 14.16% is 55 minutes. The moisture content is increased by 111.19%, and the moisturizing time is increased by 418.18%.

[0121] The water absorption rate of the viscose fiber nonwoven fabric and sodium alginate composite system (sodium alginate content 34.11%) prepared by the method of the present invention is 711.45%, and the time to reach the water content of 20.93% after dehumidification is 450 minutes. The water absorption rate of the viscose fiber nonwoven fabric of the same specification is 484.26%, and the time to reach the water content of 23.33% after dehumidification is 90 minutes. The water content is increased by 46.91%, and the moisturizing time is increased by 449%.

[0122] 2) Drug loading rate and drug release rate test

[0123] When preparing the sample of Example 1, 100% viscose spunlace nonwoven fabric with a gram weight of 40 g / m 2 , wash and dry, weigh G0, dry and weigh to get G, and get the drug loading rate according to (G-G0) / G. The test result is 13.8%.

[0124] When preparing the sample of Example 2, the medical absorbent cotton gauze was washed and dried, weighed G0, and dried and weighed to obtain G. According to (G-G0) / G and the ratio of drug to surfactant, the drug loading rate was obtained, and the test result was 7.8%.

[0125] The samples obtained in Example 1 and Example 2 were respectively placed in PBS buffer solution (pH 7.2), placed on a 37°C constant temperature shaker, and a fixed time interval was taken to measure the absorbance of the liquid by UV-Vis. Then the same volume of PBS buffer solution was added, the measurement was repeated, and the drug release rate was calculated. Figure 4 It shows that the drug release of the sample of Example 1 reaches equilibrium at 24 hours, with a release rate of 77%, and the release rate is stable and balanced within the range of 0 to 24 hours. The drug release of the sample of Example 2 reaches equilibrium at around 20 hours, with a release rate of 80%, and the release rate is stable and balanced within the range of 0 to 20 hours.

[0126] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A medical dressing comprising a fiber skeleton and a hydrogel film, characterized in that: The fiber skeleton is loaded with drug components, and the calcium alginate hydrogel forms the hydrogel membrane on the surface of the fiber skeleton. The drug components loaded by the fiber skeleton are embedded in the hydrogel membrane, and the drug components are filled in the gaps or grooves on the fiber surface. After embedding, the original gaps of the fiber skeleton are retained, and the hydrogel membrane forms a honeycomb structure.

2. The medical dressing according to claim 1, characterized in that: The mass percentage of the calcium alginate hydrogel to the fiber skeleton is 10-22%.

3. The medical dressing according to claim 2, characterized in that: The film thickness of the calcium alginate hydrogel on the surface of the fiber skeleton is 8-14 μm, and the content of the drug component is less than 25% of the weight of the fiber skeleton.

4. The medical dressing according to claim 3, characterized in that: The porosity of the fiber skeleton is 90%-95%, or the average pore size of the fiber skeleton is between 35-100 μm.

5. The method for preparing the medical dressing according to any one of claims 1 to 4, comprising the following steps: Step 1: preparing a hydrogel; dissolving sodium alginate powder in deionized water, stirring until completely dissolved, and eliminating bubbles, to obtain a sodium alginate aqueous solution; Step 2: Material selection of fiber skeleton; Step 3: drug loading treatment of fiber skeleton; Step 4: Compounding the hydrogel with the fiber skeleton: placing the drug-loaded fiber net obtained in step 3 on a transmission device, spraying the sodium alginate aqueous solution obtained in step 1 onto the drug-loaded fiber net through a nozzle; after the sodium alginate solution fully infiltrates the surface of the drug-loaded fiber net, the drug-loaded fiber net is removed from the transmission device and then immersed in a calcium chloride aqueous solution; sodium alginate and calcium ions are cross-linked and cured to form water-insoluble calcium alginate, forming an embedding film on the surface of the drug-loaded fiber net; after curing, washing with water to remove reaction byproducts; and blowing air to control the moisture content; Step 5: Drying: freeze drying is used for drying.

6. The preparation method according to claim 1, characterized in that: In step 1, the mass concentration of the sodium alginate aqueous solution is 1-3%, the solution viscosity should be less than 1000 mPa·s; the dissolution temperature is 22-50°C; the sodium alginate M / G mass ratio is 2.5-3.10; In step 2, the material of the fiber skeleton is selected from gauze and / or non-woven fabric.

7. The preparation method according to claim 1, characterized in that: In step 3, the drug is a water-soluble drug, and the processing step is step a: dissolving the water-soluble drug in deionized water, and loading the drug onto the fiber skeleton by a padding process or a spraying method to obtain a drug-loaded fiber mesh; or, in step 3, the drug is an oil-soluble drug, and the processing step is step b: selecting an oil-in-water surfactant, adding the oil-in-water surfactant and the oil-soluble drug to deionized water, and stirring at a high speed to form an oil-in-water emulsion; and loading the oil-in-water emulsion onto the fiber skeleton by a padding process or a spraying method.

8. The preparation method according to claim 7, characterized in that: Step 3 also includes a drying step; in step 3, the drug is a heat-stable water-soluble drug, and the drug-loaded fiber mesh obtained in step a is subjected to a heat drying method. After drying, the moisture content of the drug-loaded fiber mesh is controlled to be 18-25%; or, in step 3, the drug is a water-soluble drug that is easily volatile when heated, and the drug-loaded fiber mesh obtained in step a is subjected to a freeze-drying method. After drying, the moisture content of the drug-loaded fiber mesh is controlled to be 18-25%.

9. The preparation method according to claim 1, characterized in that: In step 4, the time for the drug-loaded fiber mesh to be removed from the nozzle position of the sodium alginate aqueous solution to the transmission device is 25-35 seconds; the mass concentration of the calcium chloride aqueous solution is 6-12%, and the coagulation time of the drug-loaded fiber mesh in the calcium chloride aqueous solution is 5-8 minutes.

10. The preparation method according to claim 1, characterized in that: In step 5, the freeze-drying temperature is -20°C to -30°C, and the time is 24 hours.

Citation Information

Patent Citations

  • Hydrophilic modified chitosan porous gel hemostatic gauze and its preparation method

    CN113855845B

  • A method for preparing a hydrogel gauze that prevents blood adhesion

    CN114045681B

  • Antibiotic gauze of high moisture absorption of antiseized company

    CN208541608U

  • Water-leakage-proof gel composite gauze

    CN209032850U

  • Method for preparing nano drug-carrying capsule-loaded alginate fibers

    CN103436992A